Repertory Lighting Plots. - Van Winkle, Emily (My University, 2009)
This project was based to create an advanced understanding of lighting design principles and how those principles relate to producting theatre in repertory fashion.
Repertory Light Plots in Professional Theatre.
Color poster with text, images, diagrams, and charts.
Keywords: Stage lighting; Reportory theater--Lighting; Posters